Distribution of attempted leader with monsoon seasons and negative cloud-to-ground flashes in Melaka, Malaysia - Nur Asyiqin Isa; Zikri Abadi Baharudin; Hidayat Zainuddin; Tole Sutikno; Maslan Zainon; Ahmad Aizan Zulkefle (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Ninety (90) waveforms recognized as attempted leader were identified with both positive (84 events) and negative (6 events) initial polarity observed from four consecutive years of data (N=10,206). The positive attempted leader shows no correlation with the number of thunderstorms producing it during monsoon. Meanwhile, the negative attempted leader during monsoon and both polarity of attempted leader (positive and negative) during inter-monsoon shows positive correlation with the number of thunderstorms producing it. In this study, the yearly statistical distribution of negative cloud-to-ground (CG) lightning flashes which were classified as positive preliminary breakdown pulses (214 events) and negative preliminary breakdown pulses (4982 events) in accordance of their preliminary polarity were also presented. In addition, there is no relationship of attempted leader and the initial breakdown of negative ground flash since both mechanisms performed as a negative correlation.